Efektivitas Pelaksanaan Program One Pesantren One Product (Opop) di Jawa Barat - Sugiarto, Sugiarto; Setiawati, Rosti (Universitas Koperasi Indonesia, 2022)
One Pesantren One Product (OPOP) program is the flagship program of West Java Province, which the research sites are 4 (four) champion pesantren which already have “Kopontren” spread over 4 (four) districts/cities as follows pesantren Nurul Hidayah in Kabupaten Garut, Pesantren Riyadlul Ulum in Tasikmalaya city, Pesantren Raudhatul Irfan in Kabupaten Ciamis, and Pesantren Al Muhajirin in Kabupaten Purwakarta. The results showed that the implementation of the OPOP program stages in 4 (four) pesantren as a whole was running effectively, except for the socialization stage and the training and apprenticeship stage, where at the socialization stage there were additional media or socialization facilities that were not contained in the Technical Guidelines for the OPOP program implementation such as administrators organizational areas, pesantren associations and letters from the relevant government. At the stage of training and apprenticeship there is a mismatch between the place of internship and the type of business of the pesantren.